Establishing Effective Dust Exposure Limits in Nepal: A Global Imperative for Worker Safety and Health - Mishra, A.K.; Baniya, Arjun (Journal of UTEC Engineering Management, 2024)
DOI: https://doi.org/10.36344/utecem.2024.v02i01.001To highlight the importance of implementing stringent dust exposure limits in Nepal and to propose a framework for aligning with international best practices. A comparative analysis of existing PELs for respirable crystalline silica and other dust types across several countries, including the United States, Australia, India, China, and Singapore, was conducted. The analysis focused on enforcement mechanisms, health outcomes, and regulatory frameworks. The findings reveal significant variations in PELs, with developed countries like the United States and Australia adopting stricter limits (0.050 mg/ m3) compared to India (0.150 mg/m3) and China (0.700 mg/m3). Nepal’s proposed PEL of 0.050 mg/m3 aligns with international standards but requires robust enforcement mechanisms and comprehensive monitoring strategies. Establishing effective dust exposure limits is a moral and regulatory imperative for Nepal to protect worker health. By adopting stringent PELs and enhancing regulatory frameworks, Nepal can significantly reduce the burden of dust-related diseases and promote a healthier workforce. Collaboration with international organizations and learning from the experiences of other countries will be crucial for successful implementation.